Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1037/0022-3514.73.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Psychological theory testing versus psychometric nay-saying: Comment on Neuberg et al.'s (1997) critique of the Need for Closure Scale.

Abstract: S. L. Neuberg, T. N. Judice, and S. G. West (1997) faulted our work with the Need for Closure Scale (NFCS) on grounds that the NFCS lacks discriminant validity relative to S. L. Neuberg's and J. T. Newsom's (1993) Personal Need for Structure (PNS) Scale and is multidimensional, which, so they claim, renders the use of its total score inadmissible. By contrast, the present authors show that neither of the above assertions is incompatible with the underlying need for closure theory. Relations between NFCS and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 49 publications
(142 reference statements)
6
137
0
3
Order By: Relevance
“…This issue has been fiercely debated (see, Kruglanski, De Grada, Mannetti, Atash, & Webster, 1997) but until recently, no conclusive answer on the nature of the Decisiveness scale was reached. In the meanwhile, some authors have argued that because of the non-significant relationship between Decisiveness and social attitudes, urgency strivings are not related to ideological variables (see, Kossowska & Van Hiel, 2003;Van Hiel et al, 2004).…”
Section: Is Decisiveness a Measure Of Urgency Strivings?mentioning
confidence: 99%
“…This issue has been fiercely debated (see, Kruglanski, De Grada, Mannetti, Atash, & Webster, 1997) but until recently, no conclusive answer on the nature of the Decisiveness scale was reached. In the meanwhile, some authors have argued that because of the non-significant relationship between Decisiveness and social attitudes, urgency strivings are not related to ideological variables (see, Kossowska & Van Hiel, 2003;Van Hiel et al, 2004).…”
Section: Is Decisiveness a Measure Of Urgency Strivings?mentioning
confidence: 99%
“…Webster and Kruglanski (1994) found that the correlation between Need for Closure and Personal Need for Structure was weak (r = .24), whereas and Neuberg, West, Judice, and Thompson (1997) found that it was strong (r = .79). More recently, Kruglanski et al (1997) agreed that Personal Need for Structure and the Need for Closure are correlated more strongly than they first thought (correlations of .67 to .79), but noted that 'this leaves about 50% of the variance in the two scales unexplained by their commonality ' (p. 1007). The correlation between scores on these two scales, however, is about the same as the reliabilities of the scales (.77 to .84; Neuberg & Newsom, 1993;Webster & Kruglanski, 1994), suggesting that both scales may be assessing the same thing.…”
Section: Relations Among the Constructsmentioning
confidence: 99%
“…Need for Predictability is a facet of Need for Closure and, as the name of the construct suggests, refers to a preference for having secure knowledge that implies trans-situational consistency (Kruglanski, et al, 1997;Webster & Kruglanski, 1994). Even though in non-simulated settings it is impossible to know the true value of a latent variable with certainty, there are theoretical reasons to expect that Dutch-and French-speaking Belgians do not differ substantially from each other in terms of their Need for Predictability.…”
Section: Study 2: Empirical Application Of the Calibrated Sigma Methomentioning
confidence: 99%